2021
DOI: 10.11113/lspi.v8.16906
|View full text |Cite
|
Sign up to set email alerts
|

Kemahiran Bertutur Bahasa Melayu oleh Murid Cina: Teori Analisis Kontrastif

Abstract: The acquisition of Malay as a second language, either verbally or non verbally among the non-Malay students, is still in question. It is observed that the problems of pronunciation is still prevalent among the non-Malay students. Hence, the objectives of this study are twofold; (i) to identify the level of proficiency of the speaking skill of Malay language among Chinese students, and (ii) to analyse the errors made in the speaking skill of Malay language by Chinese students based on contrastive analysis theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Mokhtar et al (2020) in their study found the effect of weak mastery of Arabic grammar will affect the construction of words and the formation of structure in sentences. Most students are weak in mastering speaking skills from various aspects, whether weaknesses stem from errors in syntax, morphology, phonology, semantics and lack of vocabulary (Fuadiya & Taufiq, 2020;Rosli et al, 2021;Ngalawi & Zainal, 2020). Weakness in mastering aspects of Arabic grammar causes students to be unable to speak Arabic fluently.…”
Section: Problem Statementmentioning
confidence: 99%
“…Mokhtar et al (2020) in their study found the effect of weak mastery of Arabic grammar will affect the construction of words and the formation of structure in sentences. Most students are weak in mastering speaking skills from various aspects, whether weaknesses stem from errors in syntax, morphology, phonology, semantics and lack of vocabulary (Fuadiya & Taufiq, 2020;Rosli et al, 2021;Ngalawi & Zainal, 2020). Weakness in mastering aspects of Arabic grammar causes students to be unable to speak Arabic fluently.…”
Section: Problem Statementmentioning
confidence: 99%